Observer - CEU Endowment and Opening Ceremony
Recording of the news presented on the Duna Televízió, M1 and RTL about the establishment of a $250 million permanent endowment for the CEU by George Soros (CEU founder and the Chairman of the Board of Trustees). The reports contain images from the press conference held at Pesti Vigadó on the 13th of October, 2001 where István Teplán (Executive Vice President of CEU) chaired the event and George Soros (Founder of CEU and the Chairman of the Board of Trustees), Yehuda Elkana (Rector and President of CEU) and Zuzana Jalcova (PhD Student) were the participants.